Non-surgical treatments for basal cell skin cancer - Alexey A. Kubanov; Rifat R. Saytburkhanov; Xenia I. Plakhova; Irina N. Kondrakhina (State Scientific Center of Dermatovenereology and Cosmetology, 2021)
Basal cell carcinoma is the most common nonmelanoma skin cancer. It originates from undifferentiated cells in the basal cell layer of the epidermis or from the outer root sheath of the hair follicle. The most important factor in development of basalioma is ultraviolet radiation. Surgery is considered the gold standard of treatment for basal cell cancer. However, nonsurgical options are available for individuals who are unsuitable for surgery. The purpose of this review is to summarize the efficacy and indications of alternative, nonsurgical treatments that can be used in the management of basal cell cancer Effective nonsurgical treatments include destructive methods (eg, curettage and electrodessication, cryosurgery, laser), photodynamic therapy, topical medications, hedgehog pathway inhibitors. Nonsurgical therapeutic alternatives are safe and effective for the treatment of BCC. Factors such as tumor location, size, and histopathological subtype should be taken into consideration when selecting optimal treatment, cosmetic results and patient preference should be considered too. To search for the necessary literature, the PubMed, MedLine, Web of Science and RSCI databases were used.